Анализ тенденций расходов на оборону в странах Латинской Америки в 2013 году - Киприч, К. К.; Ковалив, В. И.; Малахов, В. А. (НТУ "ХПИ", 2014)
У даній статті наводиться аналіз тенденцій бюджетних витрат на оборону в п'яти найбільших країнах Латинської Америки в контексті більш широкого розвитку політики в галузі оборони у 2013 році, з'ясовані зміни та витрати на оборону та на військовослужбовців у країнах Бразилії, Аргентині, Чилі, Колумбії та Мексиці. Збільшення загальних витрат на оборону країн великої п'ятірки супроводжувалось зростанням витрачань на одного військовослужбовця.

This paper presents an analysis of budget trends in defense spending in the five largest countries in Latin America in the context of a broader development policy of defense in 2013, clarifies the changes and defense spending for military personnel in such countries as Brazil, Argentina, Chile, Colombia and Mexico. The increase in overall defense spending of the big five countries has been accompanied by the growth of per-soldier spending.
Trends analysis in defense spending of Latin American countries in 2013
Keywords: оборонные расходы; вооружение; закупка вооружений; страны большой пятерки; поставщики вооружения